Circulating sex hormones and risk of atrial fibrillation: A systematic review and meta-analysis - Hu, Peng; Huang, Jun; Lu, Yi; Zheng, Murui; Li, Haiyi; Duan, Xueru; Deng, Hai; Zhao, Wenjing; Liu, Xudong (Frontiers in Cardiovascular Medicine, 2022)
Background: Sex hormones are associated with many cardiovascular risk factors, but their effects on atrial fibrillation (AF) incidence remain unclear. This study systematic review and meta-analysis aimed to evaluate the association of circulating sex hormones with AF risk by pooling available data from observational studies. Methods: A systematic literature for pertinent articles with case-control and cohort designs was conducted via five databases up to 7th July, 2021. A meta-analysis with six cohort studies was conducted separately in men and women. Adjusted relative risk (RR) with 95% confidence interval (CI) was derived by comparing the highest with lowest levels of specific sex hormone and by using a random-effect or fixed-effect model. Heterogeneity was tested using I2 statistic and Q-test. Results: A total of six cohort studies and four case-control studies were included. In meta-analysis of cohort studies, dehydroepiandrosterone sulfate (DHEAS) was associated with a decreased risk of AF in men (RR: 0.729, 95% CI: 0.559 - 0.952, I2=50.0%, P-heterogeneity = 0.157) after combining results from two cohort studies; total testosterone was not associated with any risk of AF in men and in postmenopausal women, and AF risk was not associated with estradiol in men after synthesizing available studies. Conclusions: This study indicates that higher endogenous DHEAS level was associated with lower AF risk in men, whereas total testosterone and estradiol were not associated with AF risk. Longitudinal studies with multiple monitoring are needed to further promulgate the relationship between various circulating sex hormones and AF risk.